Analysis of Trend and Forecast of The Gross Regional Domestic Product of The Agricultural Sector In Central Java Province - Syahrindra, Affan; Ekowati, Titik; Prastiwi, Wahyu Dyah (JURNAL LITBANG PROVINSI JAWA TENGAH, 2023)
The study aimed to 1). analyze the GRDP trends of the agricultural sector in Central Java Province, 2). analyze the contribution of each agricultural subsector to the formation of the agricultural sector GRDP in Central Java Province 3). analyze each district/city's contribution to the formation of the agricultural sector GRDP in Central Java Province. The research was carried out in February-March 2022 in Central Java Province. Secondary data method were used in the research. The data were obtained from Central Bureau of Statistics. Time series data on agricultural sector GRDP in Central Java Province during 2011-2020 were being used in the study. The least quadratic method were used to analyze the GRDP trends, completed with a line graph prediction of the trends. The agricultural subsector contribution analysis was conducted by calculating the contribution between the total GRDP of the agricultural subsector and the total GRDP of the agricultural sector of Central Java during Years 2011-2020. The analysis of the contribution of the district/city agricultural sector was conducted by calculating the contribution between the total GRDP of each district/city and the total GRDP of the agricultural sector of Central Java during 2011-2020. The results of the study show that the graph formed by the trend increases. The results of the agricultural subsector's contribution analysis showed that the largest contribution contributed by the food crop subsector with 34.59%, while the smallest contributed by agricultural and hunting service activities with 1.94%. The results of the contribution analysis showed that the largest contribution contributed by Brebes County with 9.02%, while the smallest contributed by Magelang City with 0.09%. In conclusion, the GRDP of the agricultural sector in Central Java Province has been on the rise and is forecast to continue to increase.